SOCIAL WORK IN THE TERRITORIAL COMMUNITY: PROBLEMS, CHALLENGES, PROSPECTS - MARTYNOVA, Liliia; YURCHУK Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the current state of social work in the Vinnytsia urban territorial community. It highlights the key issues faced by social services and outlines the urgent challenges arising from martial law, internal displacement of the population, and economic instability. The article also explores promising directions for the development of the social work system, particularly in the areas of digitalization, partnership with the non-governmental sector, and strengthening the professional capacity of social workers. The authors provide a summary, emphasizing that social work in territorial communities is a key tool for ensuring social stability, integrating vulnerable population groups, and implementing national social policy at the local level. The Vinnytsia territorial community demonstrates significant progress in introducing innovative social practices, particularly in the areas of digitalization of social services, development of an inclusive environment, expanded access to psychological support, and adaptation of internally displaced persons (IDPs). The community’s institutional capacity is continuously strengthened through participation in national and international programs (such as “City of Youth” and “Barrier-Free Environment”), which contributes to the formation of a modern, client-oriented system of social protection. Improving the professional level of social workers through systematic training and digital literacy development enhances the quality and accessibility of services. Future research directions will include the evaluation of criteria and indicators for the effectiveness of social work in the context of decentralization. Further studies are needed on the level of coordination between local authorities, social institutions, civil society organizations, and international donors. Additionally, the potential of social work to respond to the challenges of war, economic instability, and demographic change requires deeper investigation.